THE ROLE OF LONELINESS IN THE RELATION BETWEEN HEALTH AND SUBJECTIVE WELL-BEING IN OLD AGE - Rakočević, Nikolija; Gavrilov-Jerković, Vesna (Primenjena psihologija, 2017)
Loneliness is a construct which faces a growth of scientific attention in dealing with the elderly population. Although old people loose objectively numerous close or distant relations in this phase of life, loneliness is considered to be a result of a person’s subjective evaluation. When it comes to the relation of health and subjective well-being in old age, results of previous studies have been inconsistent. This research explored the manner loneliness influences the relation between old persons’ health and their level of subjective well-being. The sample consisting of 204 elderly person from the Republic of Serbia was collected during the second half of 2014. 121 participants of the total sample were female (59.3%), ranging from 65 to 92 years of age (М = 72.57). Two measures of health status (objective and subjective), individual cognitive and affective indicators of subjective well-being (life satisfaction, positive affect, negative affect, and distress) as well as measure of loneliness were administered at the same time point. Eight hierarchical regression analyses were performed on the collected data with indicators of health as predictors and loneliness as moderator. The results suggest that loneliness presents a significant deteriorating factor of good adaptation in old age. While exploring moderational roles of loneliness, only one significant interaction was gained (β = .23, p < .01). Loneliness demonstrated an interactive effect with the subjective assessment of health when it comes to evaluation of life satisfaction in the elderly. People who assessed themselves as unhealthy reported lower life satisfaction but only if they demonstrated high levels of loneliness, while this relation did not reach a level of significance if people did not perceive themselves as lonely.